Cognitive profile of ketamine-dependent patients compared with methamphetamine-dependent patients and healthy controls - Wang, Liang-Jen; Chen, Chih-Ken; Lin, Shih-Ku; Chen, Yi-Chih; Xu, Ke; Huang, Ming-Chyi (Psychopharmacology, 2018)
Background Ketamine has emerged as a major substance of abuse worldwide and has been listed with methamphetamine (METH) as two of the most widely available illicit substances in Taiwan. Only a few studies have examined the long-term consequences of chronic and heavy ketamine abuse. We compared the cognitive function of ketamine-dependent patients with that of METH-dependent patients and healthy controls. Methods We recruited 165 participants (58 ketamine-dependent and 49 METH-dependent patients who sought treatment and 58 healthy controls) and evaluated them by using a cognitive test battery, the Brief Assessment of Cognition in Schizophrenia, with scores being estimated in reference to normative data in general population. Results The ketamine-dependent patients had significantly poorer performance than did the controls in many cognitive tests, including verbal memory, motor speed, verbal fluency, and attention and processing speed, and the battery as a whole. METH-dependent patients exhibited poorer function in motor speed, verbal fluency, and attention and processing speed. The ketamine group performed poorer than did METH group in the domains of verbal memory, working memory, and attention and processing speed and the composite battery scores. A previous experience of ketamine-induced psychotomimetic symptoms, using higher doses of ketamine, and longer abstinence appeared to be associated with performance in some tests; however, the significance disappeared after multiple comparison correction. Conclusions The ketamine-dependent patients had impaired cognitive function, and METH-dependent patients exhibited intermediate performance between ketamine-dependent patients and healthy controls. Given the growing population of ketamine abusers, public education on the cognitive consequences should be provided.